Transformation of Villas to Mosques Social Impact of Islamization On The Government Center of Java In The Late 20th Century - Muh Saerozi (IJORER : International Journal of Recent Educational Research, 2021)
Islamization of Java becomes an actual topic of religious social research because the phenomena not only relate to religious discourse but also other aspects. This research focuses on the Islamization of the government center of Salatiga Central Java. The aims of this study are: to find the academic answer to why Islamization occurred in the government center of Salatiga in Central Java, to find out the Islamization process underway, to describe the dominant factors affecting Islamization, and to describe the impact of Islamization on religious life around the central government. The benefit of this research is to contribute the theories of Islamization of Government center of Java in the late of 20th century. This study is a descriptive research and causality analysis. The events were limited to those of 1985 to 2018. The data were sourced from the archives, inscription, news, interviews, and literature. The results of the study found that the Islamization of the Salatiga government center was carried out because the infrastructure was still European patterned. The actualization of Muslim religiosity was not well supported by this infrastructure. The symbol of Islamization is the transformation of the villa on the west of the city square into a mosque. The Islamization was successful because of the symbiotic factors between political parties, rulers, scholars, Islamic universities, and religious organizations. There was no significant impact yet on the improvement of spiritual and social lives around the government center. This study enriches theories about the symbiotic relations of religions, politics, and social changes in Java in the late 20th century.